AKULTURASI TRADISI TAHLILAN MASYARAKAT KECAMATAN SULABESI TIMURDALAM TINJAUAN KAIDAH ‘URF - Sanaba, M.Gadri; Abbas , Abdul Haris; Alimuddin, Harwis (IAIN Ambon, 2025)
The tahlilan tradition is one of the ritual habits of the people of East Sulabesi Subdistrict that has existed since ancient times. The tradition is carried out by reading sentences of dhikr to Allah. The people of East Sulabesi Subdistrict see the importance of carrying out the tahlilan tradition because it is believed to be part of the Islamic religion. This research aims to find out the understanding of the people of East Sulabesi Subdistrict in carrying out the tahlilan tradition, then to find out about the causes and consequences of the people of East Sulabesi Subdistrict carrying out the tahlilan tradition, and to find out the legal status of the tahlilan tradition in the perspective of the sociology of Islamic law. The method used in this research is a qualitative research method that describes the results of interviews, observations, and documentation found in the field. Then the results of the research were analyzed using the ‘Urf rule approach that “custom is an action that is continuously carried out by humans, because it is acceptable to humans, and humans repeat it continuously”. The results of this study found that the tahlilan tradition carried out by the people of East Sulabesi sub-district has a philosophy contained in general propositions. Tahlilan is performed because there are people who die, children who graduate from school, and as a gratitude to God for the achievement of their wishes. Furthermore, the tahlilan tradition carried out by the people of East Sulabesi sub-district is currently part of the shahih ‘Urf , which is a custom that does not challenge the arguments of the Qur'an and sunnah. Keywords: tahlilan tradition, ‘Urf , east sulabesi community